Nucleotide polymorphisms of the maize ZmFWL7 gene and their association with ear-related traits - Tao, Tianyun; Huang, Qianfeng; Zuo, Zhihao; Lu, Yue; Su, Xiaomin; Xu, Yang; Li, Pengcheng; Xu, Chenwu; Yang, Zefeng (Frontiers in Genetics, 2022)
Plant fw2.2-like (FWL) genes, encoding proteins harboring a placenta-specific 8 domain, have been suggested to control fruit and grain size through regulating cell division, differentiation, and expansion. Here, we re-sequenced the nucleotide sequences of the maize ZmFWL7 gene, a member of the FWL family, in 256 elite maize inbred lines, and the associations of nucleotide polymorphisms in this locus with 11 ear-related traits were further detected. A total of 175 variants, including 159 SNPs and 16 InDels, were identified in the ZmFWL7 locus. Although the promoter and downstream regions showed higher nucleotide polymorphism, the coding region also possessed 61 SNPs and 6 InDels. Eleven polymorphic sites in the ZmFWL7 locus were found to be significantly associated with eight ear-related traits. Among them, two nonsynonymous SNPS (SNP2370 and SNP2898) showed significant association with hundred kernel weight (HKW), and contributed to 7.11% and 8.62% of the phenotypic variations, respectively. In addition, the SNP2898 was associated with kernel width (KW), and contributed to 7.57% of the phenotypic variations. Notably, the elite allele T of SNP2370 was absent in teosintes and landraces, while its frequency in inbred lines was increased to 12.89%. By contrast, the frequency of the elite allele A of SNP2898 was 3.12% in teosintes, and it was raised to 12.68% and 19.92% in landraces and inbred lines, respectively. Neutral tests show that this locus wasn't artificially chosen during the process of domestication and genetic improvement. Our results revealed that the elite allelic variants in ZmFWL7 might possess potential for the genetic improvement of maize ear-related traits.